Tantangan Diversitas Sistem Pendidikan Islam di Indonesia - Kurniawati, Wakhidah; Sukari, Sukari (Lembaga Yasin AlSys, 2024)
Challenges faced by the Islamic education system in Indonesia in the context of cultural, social and economic diversity. Islamic education in Indonesia has strong roots in tradition, but is faced with issues such as inequitable access to education, quality of teaching and integration of local values in the curriculum. In addition, global changes and technological developments affect the way of learning and the needs of society. This research analyzes how Islamic educational institutions can adapt to these dynamics, as well as the importance of collaboration between the government, society and educational institutions to create an inclusive and relevant system. Through a multidisciplinary approach, this article is expected to provide insights for stakeholders in formulating policies that support the diversity and quality of Islamic education in Indonesia.